2015
DOI: 10.15403/jgld.2014.1121.244.375
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Carried microRNA-375 Inhibits Cell Progression and Dissemination via Bcl-2 Blocking in Colon Cancer

Abstract: The present study brings to the forefront new data that suggest miR-375 as a new player in controlling the pathways responsible for inhibiting the natural history of CRC tumor cells, via the Bcl-2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…Inducing apoptosis in tumor cells is believed to be a common strategy to fight against cancer (32). Other laboratories have provided evidence that exosomes or MVs could promote apoptosis in tumor cells (33,34). Our data showed that MVs induced autophagy and excessive autophagy might induce apoptosis, which explained in part the inhibitory effect of MVs on leukemia cells.…”
Section: Discussionsupporting
confidence: 55%
“…Inducing apoptosis in tumor cells is believed to be a common strategy to fight against cancer (32). Other laboratories have provided evidence that exosomes or MVs could promote apoptosis in tumor cells (33,34). Our data showed that MVs induced autophagy and excessive autophagy might induce apoptosis, which explained in part the inhibitory effect of MVs on leukemia cells.…”
Section: Discussionsupporting
confidence: 55%
“…MicroRNAs (miRNAs/miRs) are small, endogenous, non-coding RNAs composed of 18–25 nucleotides that regulate gene expression at the post-transcriptional level (1). Certain miRNAs act as oncogenes or tumor suppressors and are considered to be among the key regulators of cancer progression (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR-379 in CRC-derived exosomes has been found to down-regulate the migration of CRC cells, and transfer of these engineered miR-379-overexpressing exosomes to recipient cells reduced their migration [101]. Similarly, Zaharie et al have demonstrated that exosomal microRNA-375 inhibits tumor cell dissemination by blocking Bcl-2 in colon cancer, suggesting that exosomal microRNA-375 can be considered a potential therapeutic target [102]. Furthermore, it has been suggested since there is a positive correlation between exosomal miR-193a expression and liver metastasis of colon cancer, the major vault protein (MVP) can possibly decrease the level of circulating exosomal miR-193a, providing a new therapeutic approach for metastatic colon cancer [103].…”
Section: Exosomal Mirnasmentioning
confidence: 98%